2014
DOI: 10.1124/mol.114.095190
|View full text |Cite
|
Sign up to set email alerts
|

P-Retigabine: An N-Propargyled Retigabine with Improved Brain Distribution and Enhanced Antiepileptic Activity

Abstract: Retigabine (RTG,methyl] amino] phenyl] carbamate]) is a first-in-class antiepileptic drug that acts by potentiating neuronal KCNQ potassium channels; however, it has less than optimal brain distribution. In this study, we report that P-RTG (ethyl N-[2-amino-4-((4-fluorobenzyl) (prop-2-ynyl)amino)phenyl]carbamate), an RTG derivative that incorporates a propargyl group at the N position of the RTG linker, exhibits an inverted brain distribution compared with RTG. The brain-to-plasma concentration ratio of P-RTG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Under identical conditions, the ED 50 value of retigabine, a first-line antiepilepsy drug, was 15.0 mg/kg. 34 The MES test results suggested that these C 21 steroidal glycosides deserve further evaluation as potential candidates for the development of therapeutic agents against epilepsy. Detailed MES experimental data of these compounds are available in Table S1 (Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under identical conditions, the ED 50 value of retigabine, a first-line antiepilepsy drug, was 15.0 mg/kg. 34 The MES test results suggested that these C 21 steroidal glycosides deserve further evaluation as potential candidates for the development of therapeutic agents against epilepsy. Detailed MES experimental data of these compounds are available in Table S1 (Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mouse MES-Induced Seizure Assays. 34 KM male mice weighing 20 ± 2 g were purchased from the Shanghai Slac Laboratory Animal Co., Ltd. (Shanghai, People's Republic of China). At the conclusion of each experiment, animals were euthanized in accordance with the guidelines established by the National Institutes of Health Guide for the Care and Use of Laboratory Animals, strictly following protocols that were approved by the institutional animal care and use committees.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Since the recognition of the powerful effects of retigabine (and its close analog flupirtine) on Kv7 channels, efforts have focused on identification of Kv7 activators with distinct subtype specificity, enhanced potency, or other pharmacological properties that may enhance their utility 4,9,17,36–39 . A heterogeneous set of compounds with Kv7 activator effects has been described (comprehensively reviewed recently by Miceli et al 4 ), along with a growing understanding of their mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…As the same mice were used for all behavioral experiments, at least 2 days were given between studies to allow time for drug elimination. The plasma half-life for retigabine in mice is 7 hours (Zhou, et al, 2015) so 2 days represents more than 6 half-lives.…”
Section: Behavioral Measurementsmentioning
confidence: 99%